Series on Swedish Foreign Trade, 1780-1830 - Häggqvist, Henric (Uppsala University, 2017)
This is a data set containing series on Swedish foreign trade, from 1780 to 1830. Contains series on 37 individual import commodities, 19 export commodities, and 12 re-export commodities, on the aggregated level and by commodity. Also contains price indexes for imports and exports as well as terms of trade.

The series were published in PhD thesis On the Ocean of Protectionism: The Structure of Swedish Tariffs and Trade 1780-1830.

The dataset was originally published in DiVA and moved to SND in 2024.

Detta är ett dataset som innehåller serier om svensk utrikeshandel, från 1780 till 1830. Innehåller serier om 37 enskilda importvaror, 19 exportvaror och 12 återexportvaror, på aggregerad nivå och per vara. Innehåller även prisindex för import och export samt terms of trade.

Serierna publicerades i doktorsavhandlingen On the Ocean of Protectionism: The Structure of Swedish Tariffs and Trade 1780-1830.

Datasetet har ursprungligen publicerats i DiVA och flyttades över till SND 2024.
Series on Swedish Foreign Trade, 1780-1830
Keywords: import; import; prices; prices; Sweden; Sweden; terms of trade; terms of trade; Economic History; Economic History; export; export; foreign trade; foreign trade; Economic History; Ekonomisk historia